Experimental Research on Electrical Conductivity of the Olivine-Ilmenite System at High Temperatures and High Pressures - Sun, Wenqing; Dai, Lidong; Hu, Haiying; Wang, Mengqi; Hu, Ziming; Jing, Chenxin (Frontiers in Earth Science, 2022)
Ilmenite is a common metallic oxide distributed in the mafic rocks from the Earth’s upper mantle, and thus the effect of ilmenite contents on the electrical structures of the Earth’s upper mantle should be investigated in detail. Electrical conductivities of the olivine–ilmenite systems with various contents of ilmenite (VIlm=4, 7, 10, 11 and 15 vol.%) and pure ilmenite aggregates were measured using a complex impedance spectroscopic technique at 1.0−3.0 GPa and 773−1273 K. Electrical conductivities of the olivine–ilmenite systems increased with increasing temperatures in different degrees, conforming to the Arrhenius law. With the rise of pressure, the conductivities of the olivine–ilmenite systems slightly increased. According to the significant change of the conductivities, the percolation threshold of ilmenite grains in the olivine–ilmenite systems was proposed to be ~11 vol.%. Isolated ilmenites moderately influence the conductivities of olivine aggregates, but the interconnected ilmenites dramatically enhanced the conductivities of the olivine–ilmenite systems. The conductivities of the olivine aggregates with 11 vol.% ilmenites were about 1.5–3 orders magnitude higher than those of 10 vol.% ilmenites-bearing olivine aggregates. Small polarons were proposed to be the dominant charge carriers for olivine aggregates with isolated ilmenites (activation enthalpies: 0.62‒0.89 eV) and interconnected ilmenites (activation enthalpies: 0.15‒0.20 eV). Furthermore, the conductivity–depth profiles of olivine–ilmenite systems in the Earth’s upper mantle were constructed, providing an important constraint on the electrical structures of the Earth’s interior.